(3GdcTa hGdHjGf Yf eGAGJ GdbQBfs - (3CHh GdaQL CMeO Hf Ydj GdebQj GdgePGfjs
(3ChdgG (B:s
(3hefgG GdeaJhMI GdgeRI GdNajaI s
(3Vef eLehY , JQJjHgG (B: (3BNQ GdeLehYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B13 s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDdas
Keywords: (3GdbQGAGJ hGdJLhjOs